The Influence of Social Media Engagement on Various Outcomes - Brand Equity, Value Co-Creation and E-Word of Mouth - Dr. Aarti Deveshwar,; Rashmi, (International Journal of Engineering and Management Research, 2023)
Social media users' rising acceptance of them demonstrates that customers are developing strong emotional relationships with them. The purpose of the study to The Influence of Social Media Engagement on Various Outcomes - Brand Equity, Value Co-Creation and E-word of Mouth.